The potential of Electromotive Generator Model EM 1: a study of consumers perception and acceptance towards the product development and its marketing strategy / Hussin Hashim - Hashim, Hussin (2006)
A significant development in the electrical and electronic technology has increased in advancement day by day since from the nineteen century until now. The technology has developed tremendously from the creation of Tungsten Bulb by Sir Edison until the creation and innovation of semiconductor and robotic system in our daily live. This movement aimed to achieve the glory of latest technology. Country like U.S.A, Europe, and Japan has achieved the advancement in this technology. Nowadays, technology controlling is one of the most important elements to develop the progressive economy in every part of the world. Despite technology advancement, political stability is also important to maintain the current situation. Unstable political condition in the Middle East, Iranian Nuclear Issue, picket from the Nigerian Oil workers, strong demand for fuel in the world markets, the reduction of U.S currency compared than Euro, terrorist threat against U.S essential around the world, have caused the fuel price increased until more than U.S 68 dollar per barrel according to the Fact Number from the Berita Harian Economic Report on 02 Feb. 2006, pages 18 from this Project Paper.